2021
DOI: 10.1038/s41598-021-97760-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pulmonary microvascular structure in postnatal yaks

Abstract: Yaks are typical plateau-adapted animals, however the microvascular changes and characteristics in their lungs after birth are still unclear. Pulmonary microvasculature characteristics and changes across age groups were analysed using morphological observation and molecular biology detection in yaks aged 1, 30 and 180 days old in addition to adults. Results: Our experiments demonstrated that yaks have fully developed pulmonary alveolar at birth but that interalveolar thickness increased with age. Immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…VEGF not only increases vascular permeability but also promotes the proliferation and differentiation of vascular smooth muscle cells, thereby promoting neovascularization [68][69][70]. Together with the experimental results, the structure of the lungs determines whether yaks can adapt to the hypoxic environment of the plateau [51,71,72]. The expression of HIF-1α and VEGF in the epithelial cells of terminal fine bronchioles of yaks is relatively high compared with that in cattle, which is conducive to the protection of bronchioles and the enrichment of the soft tube mechanism in yaks under the hypoxic environment of the plateau and facilitates the contraction of bronchioles.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…VEGF not only increases vascular permeability but also promotes the proliferation and differentiation of vascular smooth muscle cells, thereby promoting neovascularization [68][69][70]. Together with the experimental results, the structure of the lungs determines whether yaks can adapt to the hypoxic environment of the plateau [51,71,72]. The expression of HIF-1α and VEGF in the epithelial cells of terminal fine bronchioles of yaks is relatively high compared with that in cattle, which is conducive to the protection of bronchioles and the enrichment of the soft tube mechanism in yaks under the hypoxic environment of the plateau and facilitates the contraction of bronchioles.…”
Section: Discussionmentioning
confidence: 83%
“…This may be closely related to the adaptation of yaks to the hypoxic environment of the plateau and reduces water consumption during respiration. At the same time, studies have shown that abundant dilated capillaries and large numbers of erythrocytes in the alveolar septa are conducive to increased alveolar ventilation and oxygen transport [51][52][53][54][55][56]. We measured the percentage of alveolar septa at all levels of the peribronchiolar alveoli in yaks after H&E, Masson, and PAS staining, observing a highly significant difference compared to that of cattle, and we also observed that the alveolar septa in yaks between adjacent alveoli was rich in capillaries, and that the number of red blood cells was higher than that of cattle.…”
Section: Discussionmentioning
confidence: 99%